The usucaptionn in the Czech and Roman law - Pavel Salák (Journal on European History of Law)
The article describes the evolution of the usucaption in civil codes on territory of Czech Republic in 19th and 20th century in the comparison to Roman Law. The bearing of the Czech legal regulation on the Roman law changed in the time. In the Austrian civil code (ABGB) we can see great influence. On the other side, the Civil Code 40/1964 Coll. deleted the institutes of possession and usucaption from the czech legal regulation and both were reverted in the novelization in 1982. From five conditions of usucaption in Roman law (res habilis, titulus, bona fides, possessio, tempus) constitutes Civil Code today res habilis, legitimate possessio and tempus. Bona fides and also titulus are included in the term "legitimate possession".